Socioeconomic status influences the toll paediatric hospitalisations take on families: a qualitative study - Beck, Andrew Finkel (BMJ Qual Saf, 2016)
BACKGROUND: Stress caused by hospitalisations and transition periods can place patients at a heightened risk for adverse health outcomes. Additionally, hospitalisations and transitions to home may be experienced in different ways by families with different resources and support systems. Such differences may perpetuate postdischarge disparities. OBJECTIVE: We sought to determine, qualitatively, how the hospitalisation and transition experiences differed among families of varying socioeconomic status (SES). METHODS: Focus groups and individual interviews were held with caregivers of children recently discharged from a children's hospital. Sessions were stratified based on SES, determined by the percentage of individuals living below the federal poverty level in the census tract or neighbourhood in which the family lived. An open-ended, semistructured question guide was developed to assess the family's experience. Responses were systematically compared across two SES strata (tract poverty rate of <15% or ≥15%). RESULTS: A total of 61 caregivers who were 87% female and 46% non-white participated; 56% resided in census tracts with ≥15% of residents living in poverty (ie, low SES). Interrelated logistical (eg, disruption in-home life, ability to adhere to discharge instructions), emotional (eg, overwhelming and exhausting nature of the experience) and financial (eg, cost of transportation and meals, missed work) themes were identified. These themes, which were seen as key to the hospitalisation and transition experiences, were emphasised and described in qualitatively different ways across SES strata. CONCLUSIONS: Families of lower SES may experience challenges and stress from hospitalisations and transitions in different ways than those of higher SES. Care delivery models and discharge planning that account for such challenges could facilitate smoother transitions that prevent adverse events and reduce disparities in the postdischarge period. Trial registration number NCT02081846; Pre-results.